2007
DOI: 10.1021/om700911a
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Decamethylhafnocene with 1,3-Butadiynes: Formation of Hafnacyclocumulenes and C−H Activation at Pentamethylcyclopentadienyl Ligands

Abstract: The reduction of Cp*2HfCl2 with lithium in the presence of disubstituted butadiynes RCC−CCR (R = Ph, SiMe3, t-Bu) in toluene leads, respectively, to the five-membered hafnacyclocumulene complexes Cp*2Hf(η4-1,2,3,4-PhC4Ph) (1-Hf) and Cp*2Hf(η4-1,2,3,4-Me3SiC4SiMe3) (2-Hf) and, in the case of 1,4-bis(tert-butyl)butadiyne by a 2-fold activation of the methyl groups of one pentamethylcyclopentadienyl ligand, to the complex Cp*Hf[−C(CCH-t-Bu)−CH(t-Bu)CH2−η5-C5Me3−CH2−] (3-Hf) containing a fulvene ligand that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…The 13 C NMR resonances of the coordinated carbon atom (C2) appear at low field ( 5 a : 171.0, 5 b : 172.1, 5 c : 175.6 ppm) and are in accordance with those previously reported for a zirconocene η 2 ‐(C,N)‐enimine complex (170.3 ppm) . Besides a titanocene fulvene complex further examples of metallocene complexes with such a η 2 ‐(C,N)‐bonded (C=C=N) unit were also reported for Nb, V and Fe …”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The 13 C NMR resonances of the coordinated carbon atom (C2) appear at low field ( 5 a : 171.0, 5 b : 172.1, 5 c : 175.6 ppm) and are in accordance with those previously reported for a zirconocene η 2 ‐(C,N)‐enimine complex (170.3 ppm) . Besides a titanocene fulvene complex further examples of metallocene complexes with such a η 2 ‐(C,N)‐bonded (C=C=N) unit were also reported for Nb, V and Fe …”
Section: Resultssupporting
confidence: 83%
“…1 H NMR spectroscopy of 3 revealed that both isocyanide ligands are equivalent, giving only one signal ( δ =2.26 ppm) for the methyl groups at the aromatic ring besides one set of signals for the rac ‐(ebthi) ligand and for the xylyl protons. The 13 C NMR resonance of the isocyanide group ( δ =248.2 ppm) is in the expected range for titanium compounds with end‐on bonded isocyanide groups . The corresponding Cp‐substituted complex [Cp 2 Ti(η 1 ‐CNXy) 2 ] shows a broadening of the signals at ambient temperature, which is not observed for 3 .…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Recently we have reported on the interactions of 1,3-butadiynes with permethylhafnocene, resulting in the formation of fivemembered hafnacyclocumulenes [1]. We were interested to investigate the reaction behaviour of these complexes especially with respect to insertion reactions, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The first crystallographically characterized tuck-over derivative in the literature, [Ti 2 (η 5 -C 5 Me 5 ) 2 ­(μ-η 5 -C 5 Me 4 ­CH 2 -κ C )­(μ-O) 2 ], was obtained by the reaction of N 2 O and a toluene solution of [Ti­(η 5 -C 5 Me 5 ) 2 ] . In contrast to the tuck-in analogous, which exhibited interesting reactivity, Bottomley’s showed a remarkable inertness toward O 2 , CO, ethylene, or even H 2 . Later, Evans reported the crystal structure of [(η 5 -C 5 Me 5 ) 2 ­Lu­(μ-H)­(μ-η 5 -C 5 Me 4 ­CH 2 -κ C )­Lu­(η 5 -C 5 Me 5 )], a tuck-over complex of an f-block element.…”
Section: Introductionmentioning
confidence: 99%